Hiradenitis suppurativa presenting as a polypoidal lesion at the anal verge - Samarasekera, D. N.; Seneviratne, S. A. (Wiley-Liss Inc, 2008)
Hidradenitis suppurativa is a chronic disease characterized by painful recurrent abscesses, fistulas and scarring lesions in axilla, groin, perineum and rarely mass lesions at the affected site. Here we present a case of hidradenitis suppurativa that presented as a polypoidal growth at the anal verge.
Keywords: Hidradenitis suppurativa; anal polyp